Study on the Impact of Water Quality from the Mebidang SPAM on Customer Satisfaction - Paschalia Retnoningtyas Surbakti; M. Ridwan Anas; Gina Cynthia Raphita Hasibuan; Anthoni Veery Mardianta; Nursyamsi Nursyamsi (Journal La Lifesci, 2025)
In 2021, the service coverage of PDAM Tirtanadi’s water supply system reached 73.3%. To further improve the service capacity, a new raw water source was developed through the construction of the Mebidang Regional Water Supply System (SPAM), which draws water from the Bingei River in Binjai City. The PDAM Tirtanadi branches directly affected by this change in raw water source include the Sei Agul and Diski branches. This study aims to evaluate customer satisfaction levels with the water product quality and service performance of the Mebidang SPAM at PDAM Tirtanadi. The methods employed include the Customer Satisfaction Index (CSI) and Importance and Performance Analysis (IPA). Data were collected through questionnaires distributed to both existing customers and new service connections at the Diski and Sei Agul branches of PDAM Tirtanadi. The results showed that customer satisfaction levels were as follows: long-term customers at the Diski branch scored 83.56%, new connections at Diski 83.57%, long-term customers at Sei Agul 82.78%, and new connections at Sei Agul 92.26%. These results indicate that both long-term and new customers at the Diski and Sei Agul branches are generally satisfied with the overall service quality. Based on the IPA results, the main priority for improvement at the Diski branch concerns the imbalance between the cost paid by customers and the volume of water received. Meanwhile, for the Sei Agul branch, variables categorized as low performance and low importance but still of lower priority include PDAM’s responsiveness to customer requests, such as for new connections or meter repairs.